PENGARUH PROFITABILITAS, SOLVABILITAS, OPINI AUDIT DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP AUDIT REPORT LAG (Pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia pada tahun 2012-2015) - Dirvi Surya Abbas; Mohamad Zulman Hakim; Roni Rustandi (COMPETITIVE, 2019)
The purpose of this study is to determine the effect of profitability, solvency, audit opinion and the size of public accountants on audit report lag. Profitability is measured by comparing earnings before tax with total assets. Solvency is measured by comparing Total Liabilities with total assets, Audit Opinions and Reputation of Public Accountants are measured using the dummy method.This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange during 2012-2015 and by using purposive sampling method. There were 48 companies during 2012-2015 that met the criteria. The analytical method used in this study is multiple regression analysis.This research result shows that profitability has no significant effect on audit report lag, while solvency, audit opinion and public accounting firm's reputation have a significant effect on audit report lag.Keywords: audit report lag, profitability, solvency, audit opinion and public accounting firm reputation..